Harnessing Sustainable Energy Transition, Eco-Tourism, and Carbonization for Effective Environmental Management: Evidence from China - Li, Yun; Islam, Muhammad Umar; Binti Hassan, Hafinaz Hasniyanti; Tirkacheva, Farangiz (International Journal of Energy Economics and Policy, 2025)
The increasing pressure from various resources such as market demand, international community participation being put on government institutions to enhance the engagement of countries in environmental initiatives. These factors, however, play distinctive roles in different development eras. Initially, it used to be viewed as an option, however, with increasing climate complexities, it has now become essential to address environmental challenges and adopt corrective measures. Ecotourism development such as introduced to safeguard environment and natural resources. However, it cannot be developed in the absence of high-quality ecotourism environment. Thereby, it is imperative to build an understanding regarding carbonization, ecotourism and energy transition to design effective environmental management and the study, in this lieu, is of greater significance to highlights the role of said constructs and provide empirical baseline from the perspective of China. The study used time series data covering the period from 1985 to 2022 and employed NARDL approach to assess the relationship. From the findings, it is revealed that ecotourism, RE output, RE consumption, industrialization, and population growth help in building effective environmental management in case of China due to positive association. Thus, offering the policy makers to take full participation in the promotion and designing of such systems so that high emitting industries are encouraged to adopt their business procedures.